Pengolahan Sampah Kertas dengan Prinsip Zero Waste pada Mahasiswa Probolinggo Jawa Timur - Fitria, Nurul Jannah Lailatul (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
Abundant paper waste and minimal management require waste management from upstream to downstream. Society needs to implement zero-waste behavior. Properly processed paper waste has potential as a recycled product with many benefits, high artistic and economic value, and is environmentally friendly. This behavior needs to be implemented in community service with the aim of community service activities to shape the community to understand, be more sensitive, and manage paper waste into recycled products to achieve zero paper waste. Service activities used a participatory action research approach with three dimensions: research, positive action, and participation. Community service activities regarding counseling on paper waste processing using zero waste principles for Probolinggo students were conducted in the creative studio for six days with 40 service partners participating. Through the circular economy concept, counseling, practice, and assistance related to paper waste can be applied to reduce, repair, reuse, recover, and recycle (5R) activities. The next stage is the 5R paper processing practice. Meanwhile, the activity evaluation results showed that all partners agreed and strongly agreed regarding service activities. The results of the evaluation of partners' understanding and abilities before and after changes in activities, partners showed increased knowledge and skills in managing paper through the 5R circular economy towards zero waste. Abstrak: Sampah kertas yang berlimpah dan minim pengelolaan membutuhkan penanganan sampah mulai dari hulu hingga hilir. Masyarakat perlu menerapkan perilaku zero waste. Limbah kertas yang diolah dengan tepat memiliki potensi besar sebagai barang daur ulang dengan banyak manfaat, bernilai seni dan ekonomi tinggi, serta ramah lingkungan. Perilaku ini perlu diterapkan pengabdian kepada masyarakat dengan tujuan kegiatan pengabdian membentuk masyarakat untuk paham, lebih peka, dan bertindak dalam mengelola limbah kertas menjadi produk daur ulang menuju zero waste kertas. Kegiatan pengabdian diselenggarakan dengan pendekatan participatory action research yang mencakup tiga dimensi: riset, aksi, dan partisipasi. Kegiatan pengabdian masyarakat tentang penyuluhan pengolahan sampah kertas dengan prinsip zero waste pada mahasiswa Probolinggo dilaksanakan di sanggar kreasi selama enam hari dengan peserta 40 mitra pengabdian. Penyuluhan dan praktik serta pendampingan terkait limbah kertas melalui konsep circular economy dapat diterapkan pada aktivitas reduce, repair, reuse, recovery, dan recycle (5R). Tahap selanjutnya adalah praktik pengolahan kertas 5R. Sementara pada hasil evaluasi kegiatan menunjukkan seluruh mitra mengatakan setuju dan sangat setuju terkait kegiatan pengabdian. Hasil evaluasi pemahaman dan kemampuan mitra sebelum dan setelah kegiatan ada perubahan, mitra menunjukkan peningkatan pemahaman dan kemampuan dalam pengelolaan kertas melalui circular economy 5R menuju zero waste. Kata kunci: Pengolahan sampah kertas, Perilaku zero-weste, Mahasiswa